(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research seeks to achieve its goal of demonstrating the impact of applying banking governance variables on the financial performance of Islamic banks, and the independent research variables are represented by (X) by (the number of independent members in the board (X1), the number of directors in the board (X2), the number of committees emanating from the board ( X3), the percentage of shares owned by major shareholders in the board (X4), the number of members of the Sharia supervisory board (X5)), and the dependent variable (Y) is represented by (rate of return on assets (Y1), rate of return on equity (Y2)). The research sample included (4) Islamic banks, namely (Iraqi Islamic Bank, National Islamic Bank, Jihan Islamic Bank, International Islamic Bank) among (15) local Islamic banks listed on the Iraq Stock Exchange, and the data were analyzed using the statistical analysis program ( SPSS-v14), and the research reached a number of conclusions, the most important of which is the practical results of the research which showed that the application of banking governance rules has a clear effect on the banking performance of Islamic banks, the research sample at the total level. , Where the CBD variable came in first place, followed by the (BOD, LBS, SSB) variants in second place, and then the BSZ variable came in the last place.